+0  
 
0
80
2
avatar

what is ; s=(u+v) x t/2

Guest Apr 5, 2017
Sort: 

2+0 Answers

 #1
avatar
0

t = (2 s)/(x (u + v)) and x (u + v) must not = 0

 

u = (2 s)/(t x) - v and t must not = 0

 

v = (2 s)/(t x) - u and t x must not = 0

Guest Apr 5, 2017
 #2
avatar
0

Sorry, I mistook * for x.

 

t = (2 s)/(u + v) and u + v must not =0

u = (2 s)/t - v and t must not =0

v = (2 s)/t - u and t must not=0

Guest Apr 5, 2017

15 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details